Trait-anxiety, depressive symptoms, family support and life satisfaction as determinants conditioning the degree of adherence of people in pre-older adults and older adults - Głowacka, Mariola; Polak-Szabela, Anna; Sienkiewicz, Zofia; Kornatowski, Maciej (Frontiers in Public Health, 2024)
The objective of the study was to determine the degree of adherence to pharmacological treatment in people in pre-older adults and older adults age groups and to analyse the correlation between selected sociodemographic parameters, severity of anxiety as a trait, symptoms of depression, a sense of family support and satisfaction with life, and adherence in people over 55 years of age. The study was conducted in a group of 2,040 people (1,406 women, 634 men) aged 55 to 100 (the average age was 65.4). The following sociodemographic variables were analysed: age, gender, education. The following scales were used: State–Trait Anxiety Inventory (STAI), Beck Depression Inventory (BDI), Satisfaction With Life Scale (SWLS) and the Multidimensional Scale of Perceived Social Support (MSPSS). The Adherence in Chronic Diseases Scale (ACDS) was used to test adherence, understood as the implementation of the therapeutic plan. The results obtained in the ACDS ranged from 6 to 28 points; the median was 24 points (21–28). The multiple coefficients of determination (multiple R2 = 0.11; p < 0.001) indicated an explanation of approximately 11% of the value of the ACDS dependent variable. The total correlation of all variables (multiple R) with the ACDS general variable in the mean correlation was 0.33. Independent factors affecting adherence assessed in the ACDS were: severity of anxiety as a trait (p = −0.21 ± 0.03; p < 0.001), family support (p = 0.10 ± 0.04; p = 0.029), severity of depression symptoms (p = −0.08 ± 0.03; p = 0.005), age of respondents (p = 0.07 ± 0.02; p = 0.003) and satisfaction with life (p = 0.06 ± 0 0.03; p = 0.027). Severity of anxiety as a trait, age, severity of depressive symptoms, a sense of satisfaction with life and family support are important factors affecting adherence.